Effects of Flow Rate and Inlet Temperature on Performance of Annulus Type Low-Temperature Latent Heat Thermal Energy Storages - Rifki Yusup; Byan Wahyu Riyandwita (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2022)
Solar energy is one of the largest energy potentials that Indonesia has, which can be utilized in solar heater that are integrated with latent heat energy storage (LHTES). This research aims to investigate the effects of the operating conditions of flow rate and inlet temperature on the performance of the annulus type Low-Temperature LHTES using Computational fluid dynamics method in which the enthalpy-porosity is used as the solidification model. The results indicate that the increase of performance can be obtained by increasing the flow rate and inlet temperature. The increase in flow rate will promote higher heat transfer thus produce better performance up to 11.91% and 24.91% during charging and discharging, respectively. Meanwhile, increasing the inlet temperature will increase the performance up to 192.72% during charging and 13.07% during discharging of the Low-Temperature LHTES system.